A Healthy Metaphor? The North Sea Consultation and the Power of Words - Haye Geukes (MDPI AG, 2021)
The North Sea Consultation was set up to resolve conflicting claims for space in the North Sea. In 2020, this consultation process resulted in the North Sea Agreement, which was supported by the Dutch Parliament and cabinet as a long-term policy; however, the fishing sector felt excluded, left the consultation process, and does not support the agreement. Using semi-constructed interviews and the method of wide reflective equilibrium, this research found that in this conflict the metaphor of ‘health’ has played a decisive role. While all stakeholders want to keep the sea ‘healthy’, they disagree on what a healthy sea actually means, leading to contrastive positions on the desirability of trawler fishing, wind parks, and conservation areas—the North Sea Agreement’s main foci of interest. To prevent the unproductive escalation of such a conflict, it is inevitable to acknowledge the moral connotations of such metaphors, as this allows a decision-making process that can be considered more just.